STUDY ON THE ADSORPTION CHARACTERISTICS OF CONGO RED BY SYCAMORE BARK ACTIVATED CARBON (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The activated carbon was prepared from sycamore bark by activation of zinc chloride. The absorbing effect of activated carbon on Congo red wastewater is studied. The characteristics of sycamore bark activated carbon were characterized by SEM and BET. The effects of adsorbent dosage, time, and shaking speed on the adsorption properties of Congo red by sycamore bark activated carbon were studied. The isotherm, kinetics, and thermodynamics of adsorption were explored. The results revealed that the activated carbon contain a large apparent mesopores. Adsorption efficiency was increased with enhancing the adsorption dosage and time. The removal rate of Conge red reached to 98.2% under room temperature with adsorbent dosage of 3.0 g/L, adsorption time of 120 min, shaking speed of 60r/min. The adsorption of Congo red on sycamore bark activated carbon was followed Langmuir isotherm model and Lagergren pseudo-second order kinetics model. The adsorption was spontaneous, endothermic, and the entropy was increasing in the adsorption process.